Robinson Crusoe - Lasson, Robert, 1922-; Defoe, Daniel, 1661?-1731.; King, Ron (Belmont, Calif. : Fearon/Janus, 1967)
An abridged version of the experiences of an Englishman stranded by shipwreck on a desert island, where he survives for some thirty years.
Wilson's Senior High School.
4.0
Young Adult
Keywords: Shipwrecks -- Fiction; Survival -- Fiction; Shipwrecks -- Fiction; Survival after airplane accidents, shipwrecks, etc. -- Fiction